Revisiting the Balkan Crisis: AUn Question; The European Connection and the Us Solution - margoto, Jackson Nyamuya (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The more fundamental decision for the States of the international community, however, was whether to make the concessions necessary to create an effective international mechanism against the background of States insisting upon preserving the totality of their sovereign prerogatives, if such aview had held sway, no effective international criminal tribunal could have been created.